Perception and safety analysis of COVID‐19 vaccination in cancer patients: A multicenter, real‐world study. (13th November 2022) - Lee, Kyoungmin; Park, In Hae; Oh, Sang Cheul; Seo, Jae Hong; Jeon, Min Ji; Yu, Eun Sang; Kim, Dae Sik; Choi, Chul Won; Lim, Ah‐reum; Hyun, Myung Han; Kim, Ju Won; Kim, Jwa Hoon; et al.
Abstract: Background: Although various coronavirus disease 2019 (COVID‐19) vaccines have been delivered to the public worldwide, data on cancer populations are limited. Vaccine hesitancy related to safety concerns is observed among cancer patients. We report the perception of COVID‐19 vaccines and their safety profile after vaccination among cancer patients. Materials and Methods: Between April and November 2021, a multicenter survey was conducted on 318 patients treated in any hemato‐oncology outpatient clinic among three hospitals under the Korea University Medical Center. The medical records of the patients were reviewed to obtain detailed clinical and hematological toxicity data. Results: A perception survey was conducted among 293 patients. Among them, 53.9% were concerned about developing vaccine‐related adverse events (VRAEs) and 23.5%, about negative effects on cancer treatment. During the study period, 255 and 186 patients participated in a safety survey after the first and second doses, respectively. After the first dose, 62% of patients reported VRAEs (2.4%, grade 3), whereas 48.9% reported VRAEs (2.7%, grade 3) after the second dose. For both doses, injection‐site pain and sore arm pain were the most common VRAEs, followed by myalgia, fatigue, and headache. No grade 4/5 VRAEs were observed, and there were no differences in complete blood count after vaccination. Multivariate analysis revealed female sex, active cancer treatment, and mRNA vaccines as independent risk factors for VRAE development in cancer patients. Conclusion: Despite high levels of concern, COVID‐19 vaccines were well tolerated by cancer patients, with a safety profile consistent with that of the general population. Abstract : Our study indicated that COVID‐19 vaccines were well tolerated and no severe adverse effects were observed in cancer patients, while there was high prevalence of fear related to vaccine‐associated adverse effects. Based on our results, we should reassure patients about the safety of COVID‐19 vaccines.